Menilai Kinerja Keuangan Berdasarkan Rasio Keuangan, Economic Value Added (EVA) And Financial Value Added (FVA) : Studi Kasus Pada BPRS AL SALAAM - Firman, Muhammad Asmeldi; Syakiriyah, Afida (SEKOLAH TINGGI EKONOMI ISLAM SEBI, 2024)
This study aims to measure the company's performance, using the analysis of financial ratios, Economic Value Added (EVA) and Financial Value Added (FVA). This study uses a qualitative descriptive method with quantitative data. This is the research method used secondary data that is collected in the form of numbers, then data were summarized, processed and analyzed, and finally descript of existing problems.The results of this study indicate that the measurement of the financial performance of BPRS Al Salaam based on the liquidity ratio performs well, the solvency ratio of the Debt to Equity Ratio (DER) and Debt to Asset Ratio (DAR) is also still too high, the activity ratio of the Total Asset Turnover (TAT) value. ) and Fix Asset Turnover (FAT) is quite good, and for the profitability ratio, the best ROA, ROE, NPM and BOPO values occurred in 2017-2019 and decreased in 2020-2021. The Economic Value Added (EVA) and Financial Value Added (FVA) values both show a positive value. This means that the company is able to create added value both economically and financiallyPada penelitian ini bertujuan untuk mengukur kinerja perusahaan, menggunakan analisis rasio-rasio keuangan, Economic Value Added (EVA) dan Financial Value Added (FVA). Penelitian ini menggunakan metode deskriptif kualitatif dengan data kuantitatif. Hasil penelitian ini menunjukkan bahwa pengukuran kinerja keuangan BPRS Al Salaam berdasarkan rasio likuiditas berkinerja baik, pada rasio solvabilitas nilai Debt to Equity Ratio (DER) dan Debt to Asset Ratio (DAR) juga masih terlalu tinggi, pada rasio aktivitas nilai Total Asset Turnover (TAT) dan Fix Asset Turnover (FAT) kurang baik, dan untuk untuk rasio profitabilitas, nilai ROA, ROE, NPM dan BOPO kinerja terbaik terjadi pada tahun 2017-2019 dan mengalami penurunan pada tahun 2020-2021. Untuk nilai Economic Value Added (EVA) dan Financial Value Added (FVA) sama-sama menunjukkan nilai yang positif. Artinya perusahaan mampu dalam menciptakan nilai tambah baik secara ekonomis maupun financialnya.